The character of training in growing the knowledge of the journey director (Czech Journal of Multidisciplinary Innovations, 2024)
In light of the raising voices calling for the necessity of the presence of the journey director in all aspects of the journey process as it is the backbone of the journey industry, and in order to maintain a journey director with special cognitive specifications, it was essential to show the character of training in increasing the knowledge of the journey director, as training is an important source of knowledge. Knowledge is an essential component of the success of the journey director in fulfilling his duties in the journey process. On this basis, the study came to idealize the character of training in increasing the knowledge of the journey director.